Political Economic Analysis of China’s Foreign Policy Changes Towards Afghanistan From 2014 to 2023 - Naomi Niken Agustina Butar-Butar; Shanti Darmastuti (Universitas Warmadewa, 2024)
China's foreign policy towards Afghanistan in the 2014-2023 period has changed in a more proactive direction. Moreover, when the Taliban succeeded in taking power in Afghanistan, China decided to maintain its concession with the country that had replaced the regime that has shown a significant change in its foreign policy towards Afghanistan, after previously freezing diplomatic relations with the country when the Taliban's first occupation occurred in the 1996-2001 period. Therefore, this research is held to determine the reasons for China's foreign policy changes towards Afghanistan from 2014 to 2023, in terms of political-economic analysis. The theory used is foreign policy, using the Goldmann model and the Holsti model approach to identify changes in China's foreign policy towards Afghanistan. The method used in this research is explanatory with data sources obtained through interviews and literature study. In the data analysis stage, the authors sort out information that is relevant to the research topic, followed by the process of presenting data and drawing conclusions. The final results of this research show that Xi Jinping is the main actor behind changes in China's foreign policy towards Afghanistan since 2014. Securing China's economic interests in the development of Gwadar Port, a significant energy infrastructure project in BRI cooperation, became one of the main considerations for Xi Jinping to change China's foreign policy towards Afghanistan.